Kinetic and mechanism studies of the adsorption of lead onto waste cow bone powder (WCBP) surfaces - Cha, J.; Cui, M.; Jang, M.; Cho, S.H.; Moon, D.H.; Khim, J. (2011)
This study examines the adsorption isotherms, kinetics and mechanisms of Pb2+ sorption onto waste cow bone powder (WCBP) surfaces. The concentrations of Pb2+ in the study range from 10 to 90 mg/L. Although the sorption data follow the Langmuir and Freundlich isotherm, a detailed examination reveals that surface sorption or complexation and co-precipitation are the most important mechanisms, along with possibly ion exchange and solid diffusion also contributing to the overall sorption process. The co-precipitation of Pb2+ with the calcium hydroxyapatite (Ca-HAP) is implied by significant changes in Ca2+ and PO4 3- concentrations during the metal sorption processes. The Pb2+ sorption onto the WCBP surface by metal complexation with surface functional groups such as ≡ POH. The major metal surface species are likely to be ≡ POPb+. The sorption isotherm results indicated that Pb2+ sorption onto the Langmuir and Freundlich constant qmax and KF is 9.52 and 8.18 mg g-1, respectively. Sorption kinetics results indicated that Pb2+ sorption onto WCBP was pseudo-second-order rate constants K2 was 1.12 g mg-1 h-1. The main mechanism is adsorption or surface complexation (≡POPb+: 61.6%), co-precipitation or ion exchange [Ca3.93 Pb1.07 (PO4)3 (OH): 21.4%] and other precipitation [Pb 50 mg L-1 and natural pH: 17%). Sorption isotherms showed that WCBP has a much higher Pb2+ removal rate in an aqueous solution; the greater capability of WCBP to remove aqueous Pb2+ indicates its potential as another promising way to remediate Pb2+-contaminated media. © 2010 Springer Science+Business Media B.V.